Hybrid Field/Transmission-Line Model for the Study of Coaxial Corrugated Waveguides - Savaidis, S.P.; Ioannidis, Z. C.; Stathopoulos, N.A. (Microwave Theory and Techniques, IEEE Transactions on, 2012)
A transmission-line model is reformulated and combined with field theory to study the propagation characteristics in coaxial waveguides with wedge-shaped corrugations, either on the outer wall or the inner conductor. Numerical results show that this equivalent-circuit approach is in agreement with conventional full-wave methods presented in the literature. Additionally, this formulation overcomes numerical issues in the calculation of higher order Bessel functions, which usually conscript sophisticated expansion techniques.
Keywords: Bessel functions; coaxial corrugated waveguides; coaxial waveguides; Conductors; Corrugated waveguides; Eigenvalues and eigenfunctions; Equations; equivalent circuits; equivalent-circuit approach; field theory; full-wave methods; gyro traveling-wave tube (gyro-TWT); higher order Bessel functions; hybrid field/transmission-line model; Impedance; Magnetic resonance; magnetron; numerical issues; Power transmission lines; propagation characteristics; transmission lines; wedge-shaped corrugations